A TaqMan real-time PCR assay for the detection and quantitation of Plasmodium knowlesi - Paul Cliff, Simon Divis; Shokoples, Sandra E; Balbir, Singh; Yanow, Stephanie K.Y (BioMed Central Ltd., 2010)
Background: The misdiagnosis of Plasmodium knowlesi by microscopy has prompted a re-evaluation of the geographic distribution, prevalence and pathogenesis of this species using molecular diagnostic tools. In this report, a specific probe for P. knowlesi, that can be used in a previously described TaqMan real-time PCR assay for detection of Plasmodium spp., and Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae and Plasmodium ovale, was designed and validated against clinical samples. Methods: A hydrolysis probe for a real-time PCR assay was designed to recognize a specific DNA sequence within the P. knowlesi small subunit ribosomal RNA gene. The sensitivity, linearity and specificity of the assay were determined using plasmids containing P. knowlesi DNA and genomic DNA of P. falciparum, P. knowlesi, P. malariae, P. ovale and P. vivax isolated from clinical samples. DNA samples of the simian malaria parasites Plasmodium cynomolgi and Plasmodium inui that can infect humans under experimental conditions were also examined together with human DNA samples. Results: Analytical sensitivity of the P. knowlesi-specific assay was 10 copies/μL and quantitation was linear over a range of 10-106 copies. The sensitivity of the assay is equivalent to nested PCR and P. knowlesi DNA was detected from all 40 clinical P. knowlesi specimens, including one from a patient with a parasitaemia of three parasites/μL of blood. No cross-reactivity was observed with 67 Plasmodium DNA samples (31 P. falciparum, 23 P. vivax, six P. ovale, three P. malariae, one P. malariae/P. ovale, one P. falciparum/P. malariae, one P. inui and one P. cynomolgi) and four samples of human DNA. Conclusions: This test demonstrated excellent sensitivity and specificity, and adds P. knowlesi to the repertoire of Plasmodium targets for the clinical diagnosis of malaria by real-time PCR assays. Furthermore, quantitation of DNA copy number provides a useful advantage over other molecular assays to investigate the correlation between levels of infection and the spectrum of disease.